Struktur Formula Anime Genre Isekai Fantasi - Ummah, Nadia Wirda; Puspitasari, Diana; Aryadillah, Muhammad (Universitas Gadjah Mada, 2024)
The isekai fantasy genre has become very popular in recent years, but there is still very little research discussing this genre. Therefore, this research attempts to formulate the basic concept of the formula structure of the isekai genre anime using genre formula studies. This research is qualitative, with data collection using documentation studies and data analysis using data reduction, selection and conclusion based on formula theory. The research formulated six basic elements that conduct the isekai genre: way to move to isekai, setting, conflict, narrative structure, hero and antagonist. The six basic elements that build the isekai genre formula in this research can be used for isekai genre formula studies. Apart from that, the isekai genre was created to meet people's tastes with an element structure that is simple and easy to understand.